Policies, Progress, and Prospects for Internet Telemedicine in China - Terence C. Cheng; Winnie Yip (Taylor & Francis Group, 2024)
Around the world, the adoption of digital technologies in health care has accelerated considerably in the wake of the COVID-19 pandemic. Prior to the emergence of the pandemic, China had already embarked on a private sector, technology enterprise-led creation of an innovative internet health care ecosystem, which has dramatically transformed China's health care landscape. In this article, we describe the evolution of China's internet health market, focusing on internet telemedicine. We trace its early origins with the establishment of information networks in the 1980s, to the emergence of a fast-growing internet health market in the 2010s that leveraged the capabilities of technology enterprises in e-commerce, logistics, and payment systems. Private health care platforms have played a central role throughout this transformative process. The supplyside of the market has a unique public-private mix structure, with the coexistence of public and private internet hospitals, and with the majority of telemedicine services provided by public hospital doctors working on private platforms in a dual practice capacity. We conclude with a discussion of the prospects of internet telemedicine, including how it should be optimized and harnessed to improve China's health system. Finally, we set out areas where more research is needed.